Is social support the key to academic buoyancy? a review of the relationship between perceived social support and academic buoyancy - Li, Danwei; Ahmad, Nor Aniza; Roslan, Samsilah (Human Resources Management Academic Research Society (HRMARS), 2024)
Academic buoyancy is the ability of a student to overcome the kinds of obstacles, pressures, and disappointments that are frequently encountered during academic study and schooling. It is considered essential for numerous academic achievement and personal wellbeing. Perceived social support are thought to play a key role in the development and display of academic buoyancy. This research aims to reviewing published studies to examine the association between perceived social support and academic buoyancy, by considering the different support types and sources. The study showed that different sources of perceived social support consistently demonstrated significant effects on academic buoyancy.